Word formation analysis of slang word expression in Freaky Friday movie script and the implication in EFL learning - Sastya Purwaningtyas, Nanda; Munifatullah, Feni; Nurdiana, Novita (English Language Education Study Program, 2025)
This study aims to investigated the word formation processes of slang word expressions found in the Freaky Friday (2003) movie script and explores their potential in supporting EFL learning. The researcher used qualitative methods, including transcription and document analysis, to collect the data. The data were analyzed using content analysis to find out each context of slang words that occur in the Freaky Friday (2003). To find out the word formation processes in each slang, the researcher used the theory by George Yule (2010). The result showed that there were 43 slang words that appear in the movie. The result of this study showed that there 43 slang words were appeared in this movie within 8 out of 10 types of word formation processes in this research. They are coinage (2%), borrowing (9%), compounding (19%), blending (5%), clipping (14%), conversion (10%), derivation (19%), and multiple processes (9%). The study highlights slang words in morphological aspects and cultural context can be implemented learners’ speaking skills and engagement. It is shown a realistic portrayal of family relationships and teenage life, making it a valuable resource for understanding the connection between language and society, especially for English learning. The researcher also classified which slang words can be suitable to be used as EFL learning material to enhance their speaking abilities.